"Tailored" antiplatelet bridging therapy with cangrelor: moving toward personalized medicine. (4th July 2022) - Valenti, Renato; Muraca, Iacopo; Marcucci, Rossella; Ciatti, Francesca; Berteotti, Martina; Gori, Anna Maria; Carrabba, Nazario; Migliorini, Angela; Marchionni, Niccolò; Valgimigli, Marco
Abstract: In the setting of patients with indication to receive dual antiplatelet therapy undergoing surgery or invasive procedures, the risk of perioperative cardiac ischemic events, particularly stent thrombosis, is high, because surgery has a prothrombotic effect and antiplatelet therapy is withdrawn in order to avoid bleeding complications. Cangrelor, an intravenous P2Y12 receptor antagonist, has been tested in a randomized trial as a "bridge" to cardiac surgery from discontinuation of oral P2Y12 receptor antagonists. Thus, a consensus document extended its off-label use in this setting and before non-cardiac surgery. Currently, despite the implementation of a standardized bridging protocol with cangrelor, a residual risk of adverse outcome mainly due to bleeding events, still persist during the perioperative phase. Accordingly, a personalized management driven by platelet reactivity serial measurements and careful assessment of ischemic and bleeding risks has potential to optimize outcomes and costs as compared to a standardized bridging protocol, based on average pharmacodynamic data of oral P2Y12 inhibitors. While specific indications for bridging have been extensively addressed in the aforementioned consensus statement, the aim of the present document is the proposal of a "tailored" clinical decision-making algorithm inspired to the principle of personalized medicine dealing with complex clinical scenarios.